2013
DOI: 10.1556/avet.2012.054
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and brainstem auditory evoked responses in the diagnosis of cerebellar cortical degeneration in american staffordshire terriers

Abstract: The aim of the study was to determine the diagnostic usefulness of magnetic resonance imaging (MRI) and brainstem auditory evoked responses (BAER) in dogs suspected of having cerebellar cortical degeneration (CCD). In the years 2009-2011, six dogs with suspected CCD were examined. Both MRI and BAER examinations revealed abnormalities in all dogs (100%). By MRI, T2-weighted midsagittal images revealed an increased amount of cerebrospinal fluid (CSF) surrounding the cerebellum within the sulci of the folia in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For the identification of inflammatory lesions the characteristics of the MRI lesion, its behaviour concerning contrast enhancement, the results of CSF analysis and blood results were considered (Tipold 1995, Kitagawa et al 2004, Platt & Olby 2004, Talarico & Schatzberg 2010, Coates & Jeffery 2014, Cardy & Cornelis 2018.Presumed infarcts and bleeding caused by traumatic brain injury or presumed microbleeds were differentiated using MRI characteristics, case history and other diagnostic tests (Platt & Olby 2004, Garosi et al 2006, Garosi 2010, Thomsen et al 2016, Kerwin et al 2017. Lesions in the brain with other aetiologies such as congenital malformation, abiotrophy or hydrocephalus were also differentiated as precisely as possible (De Lahunta & Glass 2009, Bernardino et al 2015, Bertalan et al 2014, Kwiatkowska et al 2013, Laubner et al 2015.…”
Section: Diagnostic Findingsmentioning
confidence: 99%
“…For the identification of inflammatory lesions the characteristics of the MRI lesion, its behaviour concerning contrast enhancement, the results of CSF analysis and blood results were considered (Tipold 1995, Kitagawa et al 2004, Platt & Olby 2004, Talarico & Schatzberg 2010, Coates & Jeffery 2014, Cardy & Cornelis 2018.Presumed infarcts and bleeding caused by traumatic brain injury or presumed microbleeds were differentiated using MRI characteristics, case history and other diagnostic tests (Platt & Olby 2004, Garosi et al 2006, Garosi 2010, Thomsen et al 2016, Kerwin et al 2017. Lesions in the brain with other aetiologies such as congenital malformation, abiotrophy or hydrocephalus were also differentiated as precisely as possible (De Lahunta & Glass 2009, Bernardino et al 2015, Bertalan et al 2014, Kwiatkowska et al 2013, Laubner et al 2015.…”
Section: Diagnostic Findingsmentioning
confidence: 99%
“…MRI cerebellum to total brain ratios in normal cattle and cattle affected by cerebellar hypoplasia have not been described but in dogs, the cerebellum to total brain ratio is less discriminative of cerebellar hypo-/aplasia than the brainstem to cerebellum ratio; this was reported to be 100% sensitive and specific using a cut off of 89% ( 26 , 27 ). Increased conspicuity of CSF between the cerebellar folia and an enlargement of the fourth ventricle are indicative for cerebellar hypoplasia, although this is subjective and not found in all cases regarding cerebellar disease ( 26 , 27 ). In this case, the MRI study identified several non-quantitative abnormalities that are in contrast to normal bovine brain anatomy as reported in Schmidt et al ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRI demonstrates diffuse cerebellar atrophy (Figure 9) and cerebrospinal fluid can show a mild increase in protein 105 . Brainstem auditory evoked recordings can show decreased amplitudes of waves I and II and increased inter‐wave latency for waves III to V 106 . On histopathology, obvious cerebellar atrophy is present macroscopically (cerebellum to brain ratio: 5%‐7% [normal 10%‐12%]) 108 .…”
Section: Multifocal Degenerations With Predominant (Spino)cerebellar ...mentioning
confidence: 99%
“…MRI demonstrates diffuse cerebellar atrophy (Figure 9 ) and cerebrospinal fluid can show a mild increase in protein. 105 Brainstem auditory evoked recordings can show decreased amplitudes of waves I and II and increased inter‐wave latency for waves III to V. 106 On histopathology, obvious cerebellar atrophy is present macroscopically (cerebellum to brain ratio: 5%‐7% [normal 10%‐12%]). 108 Marked loss of Purkinje neurons, with secondary thinning of the molecular and granular layers as well as increased cellularity in the cerebellar nuclei, are visible under the microscope.…”
Section: Multifocal Degenerations With Predominant (Spino)cerebellar ...mentioning
confidence: 99%
See 1 more Smart Citation